ZAKAT PROFESI BERBASIS KELUARGA SEBAGAI INSTRUMEN REDISTRIBUSI: STUDI KOMPARATIF FIQH MUAMALAH DAN HUKUM NAFAKAH UNTUK KETAHANAN EKONOMI RUMAH TANGGA - Ahmad Ahmad; Minhajuddin Madi; Muhammad Said (Al-Hukmi : Jurnal Hukum Ekonomi Syariah dan Keluarga Islam, 2025)
This study examines the management of professional zakat (zakat profesi) in urban Muslim families in Situbondo, East Java, amid the rise of the gig economy. The research aims to analyze zakat calculation mechanisms, integration with family maintenance obligations (nafakah), impacts on household economic resilience, and propose a family-based redistribution model. Employing a qualitative approach with in-depth interviews and participatory observation of 15 urban families—primarily gig workers such as online motorcycle taxi drivers and freelancers—the study reveals that 80% calculate zakat at 2.5% of net monthly income per MUI Fatwa No. 3/2003, while 60% distribute it directly to eligible relatives to strengthen kinship ties. Nafakah is prioritized by 66.7% of respondents, with 60% viewing zakat as a long-term support strategy. Digital platforms enhance compliance (r = 0.930 correlation with literacy), and integrated management boosts financial resilience in 70% of households. The proposed three-stage model—post-nafakah calculation, hybrid institutional-direct distribution, and maqasid-based evaluation—offers a sharia-compliant, fintech-enabled framework adaptable to income volatility. Findings underscore the need for enhanced syariah literacy, digital infrastructure, and collaborative policies to optimize zakat’s role in urban family welfare.